Modulating signaling networks by CRISPR/Cas9-mediated transposable element insertion - Vaschetto, Luis Maria Benjamin (2018)
In a recent past, transposable elements (TEs) were referred to as selfish genetic components only capable of copying themselves with the aim of increasing the odds of being inherited. Nonetheless, TEs have been initially proposed as positive control elements acting in synergy with the host. Nowadays, it is well known that TE movement into host genome comprises an important evolutionary mechanism capable of increasing the adaptive fitness. As insights into TE functioning are increasing day to day, the manipulation of transposition has raised an interesting possibility of setting the host functions, although the lack of appropriate genome engineering tools has unpaved it. Fortunately, the emergence of genome editing technologies based on programmable nucleases, and especially the arrival of a multipurpose RNA-guided Cas9 endonuclease system, has made it possible to reconsider this challenge. For such purpose, a particular type of transposons referred to as miniature inverted-repeat transposable elements (MITEs) has shown a series of interesting characteristics for designing functional drivers. Here, recent insights into MITE elements and versatile RNA-guided CRISPR/Cas9 genome engineering system are given to understand how to deploy the potential of TEs for control of the host transcriptional activity.